Phosphate Solvent Fungi Exploration and Identification in West Bali National Park Forest Area - Priyanta, Riswanda Dwiky; Proborini, Meitini Wahyuni; Dalem, Anak Agung Raka (Metamorfosa: Journal of Biological Sciences, 2019)
Research on the exploration and identification of phosphate solvent fungi has never been carried out in West Bali National Park (TNBB), therefore researchers aims to explore and identify microscopic fungi to be used as phosphate solvent fungi which later will be taken from each plant soil samples ( Lantana camara ) that the presence is very common in TNBB. The research was implemented in two stages. The first stage is exploration of soil fungi in the field (TNBB) and identification of fungal species and the second stage is the phosphate solvent fungus test on Pikovskaya media. The results of the identification of the fungi obtained as follow: Aspergillus niger, Aspergillus bertholletius, Aspergillus flavus, Aspergillus isolate 4, Aspergillus isolate 5, Penicillium citrinum, and Trichoderma amazonicum. From the entire types of fungi obtained, there are onlybfour fungi that have the potential as phosphate solvents, namely Aspergillus niger, Aspergillus flavus, Aspergillus bertholletius and Penicillium citrinum with the presence of clear zones on Pikovskaya media. Fungi that has the best potential in the process of phosphate dissolution is Aspergillus niger.   Key words : Rhizosfer, Lantana camara , clear zone , phosphate solvent fungus